2021
DOI: 10.3390/biomedicines9091191
|View full text |Cite
|
Sign up to set email alerts
|

Iron Replacement and Redox Balance in Non-Anemic and Mildly Anemic Iron Deficiency COPD Patients: Insights from a Clinical Trial

Abstract: In COPD patients, non-anemic iron deficiency (NAID) is a common systemic manifestation. We hypothesized that in COPD patients with NAID, iron therapy may improve systemic oxidative stress. The FACE (Ferinject assessment in patients with COPD and iron deficiency to improve exercise tolerance) study was a single-blind, unicentric, parallel-group, placebo-controlled clinical trial (trial registry: 2016-001238-89). Sixty-six patients were enrolled (randomization 2:1): iron arm, n = 44 and placebo arm, n = 22, with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 64 publications
1
20
0
Order By: Relevance
“…All the participants were diagnosed according to the Global Strategy of Management of COPD patients (GOLD) criteria, in which the following parameters were included: spirometry values, number of exacerbations, and dyspnea score (modified medical research council, mMRC) [ 24 ]. Iron-deficient COPD patients (12 males) presented levels of hemoglobin > 12 g/dL in women and >13 g/dL in men, ferritin < 100 ng/mL, or ferritin 100–299 ng/mL with a transferrin saturation < 20% [ 21 , 23 , 25 , 26 ]. The study was approved on 17 January 2018 by the local Ethics Committee at Hospital del Mar (CEIm Parc de Salut Mar, registration # 2017/7691/I).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…All the participants were diagnosed according to the Global Strategy of Management of COPD patients (GOLD) criteria, in which the following parameters were included: spirometry values, number of exacerbations, and dyspnea score (modified medical research council, mMRC) [ 24 ]. Iron-deficient COPD patients (12 males) presented levels of hemoglobin > 12 g/dL in women and >13 g/dL in men, ferritin < 100 ng/mL, or ferritin 100–299 ng/mL with a transferrin saturation < 20% [ 21 , 23 , 25 , 26 ]. The study was approved on 17 January 2018 by the local Ethics Committee at Hospital del Mar (CEIm Parc de Salut Mar, registration # 2017/7691/I).…”
Section: Methodsmentioning
confidence: 99%
“…These findings were directly associated with both disease severity and the loss of mitochondrial content. Serum hepcidin was also shown to be a surrogate biomarker of iron status and metabolism in patients with chronic respiratory diseases including COPD [ 21 ]. Iron deficiency in COPD was also associated with reduced physical activity [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Monitoring markers of oxidative stress and miR genotyping for precision-based chemotherapy [10] Iron-deficient COPD IV iron replacement Monitoring hepcidin as a marker for non-anaemic iron deficiency [23] Antimicrobial-resistant COPD Targeted antibiotics based on culture sensitivities Use of colour charts to determine commencement of antibiotics [14] Key-LABA: long-acting β-agonists; LAMA: long-acting muscarinic antagonists; ICS: inhaled corticosteroids; HRQoL: health-related quality of life; CFTR: cystic fibrosis transmembrane receptor; miR: microRNA; VTE: venous thromboembolism; NIV: noninvasive ventilation; OSA/ORRF: obstructive sleep apnoea/obesity-related respiratory failure; COPD: chronic obstructive pulmonary disease; IV: intravenous.…”
Section: Subgroup Established Treatment Future Management Considerationsmentioning
confidence: 99%
“…As in the trial by Pérez-Peiró et al, these parameters can be measured biochemically by monitoring indirect markers of oxidative stress and antioxidants [ 23 ]. The authors demonstrated a decline in oxidative stress markers in non-anaemic COPD patients randomised to intravenous iron replacement within a short four-week study.…”
Section: Comorbiditiesmentioning
confidence: 99%
“…Non-anemic iron deficiency (NAID) is a common metabolic disorder, affecting between 18% and 48% of subjects with chronic obstructive pulmonary disease (COPD). 1 , 2 Among the known pulmonary vascular effects of NAID are intracellular oxidative stress dysregulation, 3 pulmonary arterial smooth muscle proliferation, 4 and hyperreactive hypoxic pulmonary vasoconstriction (HPV). 5 Thus, NAID could be associated with increased systolic pulmonary arterial pressure (sPAP) under resting conditions in COPD subjects.…”
Section: Introductionmentioning
confidence: 99%